Valuing landscape in classical antiquity: natural environment and cultural imagination - McInerney, Jeremy; Sluiter, Ineke (Mnemosyne, 2016)
Front Matter /Jeremy McInerney and Ineke Sluiter -- General Introduction /Jeremy McInerney and Ineke Sluiter -- Mount Etna in the Greco-Roman imaginaire: Culture and Liquid Fire /Richard Buxton -- Strabo’s Mountains /Jason König -- Mountain, Myth, and Territory: Teuthrania as Focal Point in the Landscape of Pergamon /Christina G. Williamson -- Diving Underground: Giving Meaning to Subterranean Rivers /Julie Baleriaux -- Experience and Stimmung: Landscapes of the Underworld in Seneca’s Plays /Kathrin Winter -- Birds around the Temple: Constructing a Sacred Environment /Margaret M. Miles -- Juno Sospita and the draco: Myth, Image, and Ritual in the Landscape of the Alban Hills /Rianne Hermans -- Charismatic Landscapes? Scenes from Central Greece under Roman Rule /Betsey A. Robinson -- Heritage in the Landscape: The ‘Heroic Tumuli’ in the Troad Region /Elizabeth Minchin -- Land at Peace and Sea at War: Landscape and the Memory of Actium in Greek Epigrams and Propertius’ Elegies /Bettina Reitz-Joosse -- Thessaly as an Intertextual Landscape of Civil War in Latin Poetry /Annemarie Ambühl -- Migration and Landscapes of Value in Attica /Danielle L. Kellogg -- Songs of Homecoming: Sites of Victories and Celebrations in Pindar’s Victory Odes /Maša Ćulumović -- The Mythical Landscapers of Augustan Rome /Lissa Crofton-Sleigh -- Polyvalent Tomi: Ovid’s Landscape of Relegation and the Romanization of the Black Sea Region /Christoph Pieper -- Stones, Names, Stories, and Bodies: Pausanias before the Walls of Seven-Gated Thebes /Greta Hawes -- Indexes /Jeremy McInerney and Ineke Sluiter.
Description based upon print version of record
Keywords: Religionsgeografie; Kollektives Gedächtnis; Landschaft; Antike; Kulturlandschaft; Römisches Reich; Griechenland